1979
DOI: 10.1152/ajpregu.1979.236.3.r221
|View full text |Cite
|
Sign up to set email alerts
|

Blood oxygen transport and organ weights of two shrew species (S. etruscus and C. russula)

Abstract: Blood parameters concerning oxygen transport and relative organ weights of 11 Suncus etruscus and 13 Crocidura russula under light halothane anesthesia were investigated. Mean body weight of S. etruscus was 2.5 g and for C. russula was 9 g, hemoglobin concentration was 17.4 and 15.6 g/100 ml blood, hematocrit was 50 and 44%, red blood cells were 18 and 11 X 10(6)/microliter, respectively. Mean corpuscular volume was calculated to be 26 and 41 micron3, mean diameter 5.5 and 7 micron, and mean thickness 1.2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…These authors further suggested that the high rate of proton generation at the tissues arising from this reaction, coupled with a relatively high Bohr factor, may allow the blood O 2 stores of small mammals to be more fully exploited. Consistent with these predictions, measured Bohr coefficients of shrew Hb and blood (-0.61 to -0.69) are at the upper range for mammals (Bartels et al 1979;Jürgens et al 1981; this study). However, our findings regarding the dual modulation of Episoriculus Hb by phosphate and chloride ions, together with its low thermal sensitivity and predicted low proton buffering capacity, suggest that the functional control of O 2 uptake and delivery in these diminutive insectivores may be more complex than previously suspected.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…These authors further suggested that the high rate of proton generation at the tissues arising from this reaction, coupled with a relatively high Bohr factor, may allow the blood O 2 stores of small mammals to be more fully exploited. Consistent with these predictions, measured Bohr coefficients of shrew Hb and blood (-0.61 to -0.69) are at the upper range for mammals (Bartels et al 1979;Jürgens et al 1981; this study). However, our findings regarding the dual modulation of Episoriculus Hb by phosphate and chloride ions, together with its low thermal sensitivity and predicted low proton buffering capacity, suggest that the functional control of O 2 uptake and delivery in these diminutive insectivores may be more complex than previously suspected.…”
Section: Discussionsupporting
confidence: 85%
“…Under presumed intracellular conditions (pH 7.2 and 37°C) the P 50 of Episoriculus Hb devoid of anions (7.7 mmHg) is *75 % higher than that recorded for human HbA (4.4 mmHg; Perutz and Imai 1980) under the same conditions, and only half of that reported for 'stripped' hemolysates of S. etruscus and C. russula (13.1 and 17.4 mmHg respectively; Bartels et al 1979). Notably, however, these latter samples were eluted in 0.16 M Cl -Tris buffer (Jür-gens et al 1981) and thus are likely more comparable to values obtained from E. fumidus Hb in the presence of 0.1 M Cl -(14.8 mmHg; Table 1).…”
Section: Oxygen Affinitymentioning
confidence: 71%
See 3 more Smart Citations